Distal locking of short cephalomedullary nails decreases varus collapse in unstable intertrochanteric fractures – a biomechanical analysis. Issue 3 (March 2021) - Tisherman, Robert T.; Hankins, Margaret L.; Moloney, Gele B.; Tarkin, Ivan S.
Highlights: In capacious femoral canals (Dorr C), unlocked short cephalomedullary screws show increased varus collapse. There is no difference in varus collapse in narrow or capacious femoral canals with locked short cephalomedullary screws. Specific patients with osteoporotic bone may benefit from distal cross-locking of short cephalomedullary nails. Abstract: Introduction: Peritrochanteric fractures are a growing problem and complications relating to operative fixation of these fracture, including varus collapse and screw cutout, are common in elderly osteoporotic patients. We hypothesize that unlocked nails will demonstrate increased varus collapse and inferior construct stiffness in specimens with increased diaphyseal medullary diameter. Materials and methods: Sixteen non-cadaveric osteoporotic biomechanical femur specimens were utilized in this study, with eight specimens having an artificially large femoral canal to represent Dorr C femurs. All femurs were instrumented with a short cephalomedullary nail with and without distal cross-lock screw fixation and had an unstable intertrochanteric fracture created in a repeatable pattern. Specimens underwent cyclic compression to a maximal load of 1000N with segmental motion quantified through the use of visual tracking markers. Statistical comparisons were performed using one-way ANOVA with Tukey post-hoc analysis to determine differences between specific groups. Significance was defined as p<0.05. Results: Unlocked short cephalomedullary nails showed increased varus collapse due to motion of the nail within the femoral canal in capacious femoral canals compared with narrow femoral canals and distally cross-locked nails. The coronal deformation of the wide canal unlocked group (17.9 o ±2.6 o ) was significantly greater in the varus direction than any other fixation under compressive load of 1000N. There was no significant difference in varus angulation between the wide canal or narrow canal locked groups (11.1 o ±8.7 o vs. 8.2 o ±1.7 o respectively, p=0.267). The narrow canal unlocked group (13.7 o ±2.4 o ) showed significantly greater varus angulation than the narrow canal locked (p=0.015). The wide canal unlocked group showed significantly greater varus angulation than the wide canal locked group (p=0.003). Motion between the femoral shaft and the cephalomedullary nail (toggling of the nail within the shaft) was significantly greater in narrow or wide canal unlocked specimens, 7.94 o ±2.13 o and 10.2 o ±1.7 o respectively, than in the narrow or wide canal locked specimens, 2.4 o ±0.2 o and 4.2 o ±0.5 o respectively (p<0.05) Conclusion: Unlocked short intramedullary fixation for unstable peritrochanteric fractures results in increased varus collapse under axial compression. This study supports the use of distal cross-locking of short intramedullary fixation for unstable peritrochanteric fractures in patients with capacious femoral canals secondary to osteoporosis who might otherwise be as risk for varus collapse, device failure, and malunion.